Adipokines and Their Role in Intestinal Inflammation - Weidinger, Carl; Ziegler, Jörn F.; Letizia, Marilena; Schmidt, Franziska; Siegmund, Britta (Frontiers in Immunology, 2018)
Fat tissue was initially described for its endocrine and metabolic function. Over the last two decades increasing evidence indicated a close interaction with the immune system. Partly responsible for this immunodulatory function is soluble factors released by the fat tissue, most prominently the so-called adipokines. These discoveries led to the question how adipokines influence inflammatory diseases. Linking inflammation and adipose tissue, Crohn's disease, a chronic inflammatory bowel disease, is of particular interest for studying the immune modulatory properties of adipokines since it is characterized by a hyperplasia of the mesenteric fat that subsequently is creeping around the inflamed segments of the small intestine. Thus, the role of several adipokines in the creeping fat as well as in intestinal inflammation was recently explored. The present review selected the four adipokines adiponectin, apelin, chemerin and leptin and provides a working model based on the available literature how these factors participate in the maintenance of intestinal immune homeostasis.